The role of kenaf and montmorillonite clay on the enhancement of the properties of polyhydroxybutyrate composites / Muhammad Rafiq Mohd Isa - Muhammad Rafiq , Mohd Isa (2022)
Kenaf reinforced and montmorillonite (MMT) modified polyhydroxybutyrate (PHB) composites were prepared using a twin-screw extruder and injection moulding machine. The influence of reinforcement content and surface treatment on the composites' mechanical, rheological and thermal properties was investigated. The samples were moulded into a bar and dumb-bell shaped specimens and subjected to dry-as-moulded, indoor, outdoor and soil burial conditions for four months. The composites were characterised for thermal, rheological and mechanical properties. The results were supported by images obtained from microscopy techniques such as field emission scanning electron microscopes (FESEM) and transmission electron microscopes (TEM). Weibull analysis of single fibre tensile test results indicates fibre damage due to a high concentration of sodium hydroxide or longer soak time. Kenaf reinforced PHB exhibited up to 21% improvement in Young’s modulus. The presence of fibres in the polymer melt modified its flow behaviour from Newtonian (in pure PHB melt) to shear thinning behaviour. Fracture energy and critical strain energy release rate of the kenaf reinforced composite was increased with the addition of 20% kenaf fibres. FESEM image showed gaps between the PHB matrix and treated kenaf fibres, indicating that interfacial adhesion is still poor. However, the melt behaviour, such as the complex viscosity and storage modulus obtained through the rheological study of the treated kenaf PHB composites, shows improvement in interaction. Long term mechanical properties of treated kenaf composites also showed better performance. Energy dispersive X-ray mapping revealed that nanocomposites with clay content of 3 phr exhibited better dispersion than nanocomposites with higher clay content. The mechanical properties of the MMT-modified PHB, such as the tensile and flexural modulus, were enhanced compared to neat PHB. From the rheological study, PHB and PHB nanocomposites modified with untreated MMT exhibited Newtonian fluid behaviour in the tested frequency range. However, for nanocomposites modified with acid-treated MMT, shear-thinning behaviour was observed at higher clay content. The nanocomposites also exhibited higher complex viscosity compared to PHB. From transmission electron microscopy analysis, exfoliation of the MMT was observed for the treated MMT nanocomposites at all clay loading. MMT-modified PHB has lower melting temperature when compared to neat PHB. Furthermore, it was found that the addition of MMT influenced the crystallisation behaviour of PHB. The presence of acid-treated MMT also reduced the degree of crystallinity with increasing clay content. MMT modification of PHB was shown to reduce the rate of PHB biodegradation when buried in the soil.